An international perspective on organisational strategies to foster skill-mix changes in healthcare. (13th November 2019) - Kroezen, M; Dussault, G; Gericke, C; Kuhlmann, E
Abstract: Background: The implementation of skill-mix innovations in healthcare organisations is a complex process which many factors affect, positively or negatively. Facilitators are factors which stimulate or expand skill-mix change, whereas barriers are factors that limit or restrict skill-mix change. This study provides an overview of the most common facilitators and barriers. Methods: An overview of systematic reviews was conducted as part of a larger project studying skill-mix innovations. 20 reviews on organisational-level factors related to the implementation of skill-mix innovations were included. The evidence from the reviews was supplemented with country case studies. Results: Organisational factors, such as physical proximity of services involved in the skill-mix or well-functioning information systems, are often discussed in the literature on skill-mix implementation at organisational level. The same applies to individual factors, such as required knowledge levels or (lack of) trust. Process factors and characteristics of the skill-mix intervention seem to play a less important role, even though coaching and support for professionals seem to facilitate the implementation process. The institutional environment mainly seems to have a hampering effect, especially related to a lack of financing, reimbursement issues or perceived fears of liability. Often, the implementation of skill-mix interventions at organisational level is approached by focusing on specific facilitators and barriers, yet little attention is paid to structural approaches. Conclusions: There is no single appropriate strategy for implementing skill-innovations that will fit all organisations. Managers must adopt an optimal strategy when implementing skill-mix, usually involving a combination of approaches best suited to local factors, to their specific organisational context and to the individuals involved.